2007
DOI: 10.1118/1.2409239
|View full text |Cite
|
Sign up to set email alerts
|

An arc‐sequencing algorithm for intensity modulated arc therapy

Abstract: Intensity modulated arc therapy (IMAT) is an intensity modulated radiation therapy delivery technique originally proposed as an alternative to tomotherapy. IMAT uses a series of overlapping arcs to deliver optimized intensity patterns from each beam direction. The full potential of IMAT has gone largely unrealized due in part to a lack of robust and commercially available inverse planning tools. To address this, we have implemented an IMAT arc-sequencing algorithm that translates optimized intensity maps into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
65
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 31 publications
0
65
0
Order By: Relevance
“…( 12 , 54 , 57 , 58 ) Recent studies ( 18 , 25 ) on 65 HN cancer patients reported that multiple arcs were needed for such patients. For the more complex HN cancer cases, Shepard et al ( 18 , 19 ) concluded that the use of two arcs was necessary, leading to equivalent results as IMRT. Similar to other IMRT/VMAT planning reports, those found that tumors in HN regions, mainly NPC cases, were the most challenging cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…( 12 , 54 , 57 , 58 ) Recent studies ( 18 , 25 ) on 65 HN cancer patients reported that multiple arcs were needed for such patients. For the more complex HN cancer cases, Shepard et al ( 18 , 19 ) concluded that the use of two arcs was necessary, leading to equivalent results as IMRT. Similar to other IMRT/VMAT planning reports, those found that tumors in HN regions, mainly NPC cases, were the most challenging cases.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying VMAT planning engine in both SmartArc and Oncentra MasterPlan TPS is the same as that developed by RaySearch, and the dose calculation algorithms of pencil beam (PB) convolution and collapsed cone convolution (CCC) were chosen. ( 18 , 19 ) …”
Section: Introductionmentioning
confidence: 99%
“…( 1 ) It allows simultaneous variation of dose rate, gantry speed, and multileaf collimator (MLC) segments. ( 2 ) The technique promises some dosimetric benefits ( 3 ) together with reduced treatment times ( 1 , 2 , 4 6 ) which, in turn, may have significant radiobiological impact. ( 7 9 ) …”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] The theoretical framework of VMAT was originally introduced in 1995 by Yu 5 as intensity modulated arc therapy (IMAT), which generated multiple MLC segments per beam angle and requires multiple arcs to deliver. [6][7][8] More practical single arc VMAT algorithms were subsequently developed 9-11 including a representative publication by Otto. 12 Compared to the static beam IMRT problem, the arc optimization problem was considered significantly more complex, due both to the substantially increased beam orientations and the additional machine mechanical constraints such as gantry and MLC mechanical limits.…”
Section: Introductionmentioning
confidence: 99%